Beyond Halal Certification: Restaurant Standards, Spatial Governance, and Tax Compliance in Islamic Economic Perspective - Surya, Muhammad Arsyadillah; Setiawan, Jerry Wahyu; Amalia, Kuni Katika; Khulsum, Umi; Arsyad, Abd Rahim (Bertuah Jurnal Syariah dan Ekonomi Islam, 2025)
Studies on halal standards in restaurants have generally focused on certification, the halalness of raw materials, and compliance with production processes. This approach is important, but it does not fully reflect the complexity of business governance from an Islamic economic perspective. This article starts from the assumption that halal standards cannot be understood simply as certificate ownership, but rather as a system encompassing space management, operational management, and compliance with fiscal obligations. This research uses a qualitative literature review method by examining various sources related to halal regulations, food service industry spatial planning, and tax compliance within the framework of Islamic economic law. The study's findings indicate that halal integrity is closely related to kitchen zoning, production process separation, hygiene standards, and supply chain oversight. Furthermore, tax compliance, from an Islamic economic perspective, can be interpreted as part of social responsibility and a contribution to the public good. Therefore, halal standards for restaurants need to be placed within a broader governance framework, simultaneously integrating religious, regulatory, and socio-economic dimensions. This article offers a conceptual contribution by reconstructing halal standards as a multidimensional system that not only guarantees product legitimacy but also reflects the principles of fairness, responsibility, and sustainability in business practices. The proposed framework is expected to enrich academic discourse and serve as a reference for regulators and business actors in developing more comprehensive restaurant governance that aligns with Islamic economic values.